Assessment of small sensory fiber function across the spectrum of severity in carpal tunnel syndrome patients. Issue 4 (21st March 2017) - Clarke, Christopher; Christensen, Christopher; Curran, Matthew W.T.; Chan, K. Ming
ABSTRACT: Introduction : In compressive neuropathies, large myelinated nerve fibers are generally thought to be more susceptible. In this study, we investigated small myelinated Aδ and unmyelinated C fiber function in patients with mild, moderate, and severe carpal tunnel syndrome. Methods : Forty‐four healthy controls and 81 carpal tunnel syndrome patients in the mild, moderate, or severe categories were recruited. Small fiber sensation in the affected hand was determined with quantitative sensory testing. Results : Cold detection thresholds in the severe carpal tunnel syndrome group (18.9 ± 6.8°C) were significantly impaired compared with controls (27.2 ± 2.1°C) ( P < 0.01). Similarly, warm detection thresholds were also impaired in the severe carpal tunnel syndrome group (41.2 ± 3.5°C) compared with control (37.1 ± 2.1°C) ( P < 0.01). Conclusions : These results support the growing body of evidence that carpal tunnel syndrome can affect small afferent fibers. Muscle Nerve 56 : 814–816, 2017